Recovery of iron from sludge using solid phase materials - Mohd Qasmal Mohd Noor (Universiti Malaysia Perlis, 2008)
The application of metals extraction by polymer inclusion membrane (PIMs) was carried out by using solid phase materials. The ion carrier Cyanex 272 was incorporated into solid phase materials composed of cellulose triacetate (CTA) as support polymer and tetrachloro methane (TCM) as solvent. Extraction of iron was done by shaking the beaker containing iron sulphate solution and the solid phase materials by using the magnetic stirrer for 30 minutes. The solution gain from the extraction process undergoes Atomic Absorption Spectrometer (AAS) test to determine its concentration. This concentration was then compared with the initial solution concentration to calculate the percent of extraction. Fifteen experiments were being done to see the effect of different variables to the percent of extraction. These variables are pH, amount of solid phase materials and temperature. Results obtained show that increasing in all of the three variables one by one while keeping the other two constant, give an increase in the percent of extraction. From the data gained, the optimum condition which results in 99.5 % of iron extraction was obtained.